Antifungal and Anti-Biofilm Effects of Caffeic Acid Phenethyl Ester on Different Candida Species - Ibrahim Alfarrayeh; Edit Pollák; Árpád Czéh; András Vida; Sourav Das; Gábor Papp (MDPI AG, 2021)
This study investigated the effect of CAPE on planktonic growth, biofilm-forming abilities, mature biofilms, and cell death of C. albicans, C. tropicalis, C. glabrata, and C. parapsilosis strains. Our results showed a strain- and dose-dependent effect of CAPE on Candida, and the MIC values were between 12.5 and 100 µg/mL. Similarly, the MBIC values of CAPE ranging between 50 and 100 µg/mL highlighted the inhibition of the biofilm-forming abilities in a dose-dependent manner, as well. However, CAPE showed a weak to moderate biofilm eradication ability (19-49%) on different Candida strains mature biofilms. Both caspase-dependent and caspase-independent apoptosis after CAPE treatment were observed in certain tested Candida strains. Our study has displayed typical apoptotic hallmarks of CAPE-induced chromatin margination, nuclear blebs, nuclear condensation, plasma membrane detachment, enlarged lysosomes, cytoplasm fragmentation, cell wall distortion, whole-cell shrinkage, and necrosis. In conclusion, CAPE has a concentration and strain-dependent inhibitory activity on viability, biofilm formation ability, and cell death response in the different Candida species.